(untitled) (Información, cultura y sociedad, 2004)
In the framework of the agreement between the Universidad de Campinas and the University of Buenos Aires, we visited the UNICAMP, as a part of a six members commission representing various areas of research and information management of the Faculty. The present work aims at implementing the experience gathered during the visit to the Library System of Universidad de Campinas. We pay special attention to issues concerning “culture of cooperative work” and “development of consortiums”, which we consider two key tools for achieving a better utilization of the available resources in the management of information.